Phage-derived peptidoglycan degrading enzymes: challenges and future prospects for in vivo therapy - Oliveira, Hugo (2018)
Peptidoglycan degrading enzymes are of increasing interest as antibacterial agents, especially against multi-drug resistant pathogens. Herein we present a review about the biological features of virion-associated lysins and endolysins, phage-derived enzymes that have naturally evolved to compromise the bacterial peptidoglycan from without and from within, respectively. These natural features may determine the adaptability of the enzymes to kill bacteria in different environments. Endolysins are by far the most studied group of peptidoglycan-degrading enzymes, with several studies showing that they can exhibit potent antibacterial activity under specific conditions. However, the lytic activity of most endolysins seems to be significantly reduced when tested against actively growing bacteria, something that may be related to fact that these enzymes are naturally designed to degrade the peptidoglycan from within dead cells. This may negatively impact the efficacy of the endolysin in treating some infections in vivo. Here, we present a critical view of the methods commonly used to evaluate in vitro and in vivo the antibacterial performance of PG-degrading enzymes, focusing on the major hurdles concerning in vitro-to-in vivo translation.